Pengaruh Penerapan Sanksi Perpajakan Dan Layanan E-Samsat Terhadap Kepatuhan Wajib Pajak Dalam Pembayaran Pajak Kendaraan Bermotor Di Kantor Samsat Medan Utara - Ariska, Sinta; Sahnan, M.; Rahmarisa, Faty; Iriani, Iriani (Universitas Islam Sumatera Utara, 2024)
This study aims to determine (1) the effect of the application of tax sanctions on taxpayer compliance and (2) the effect of e-samsat services on taxpayer compliance. The subjects of this study are all taxpayers in North Sumatra. This research is populative with 100 respondents. Data collection method through questionnaire survey. The data analysis techniques used in this study are validity and reality tests, classical assumption tests, multiple linear regression analysis, T test and F test and determination coefficient test.The results showed that (1) Application of Tax Sanctions Based on the processed data, the attitude of sanctions gave a calculated t result of 1700 1,984. So it can be concluded that the Application of Tax Sanctions has a positive effect on taxpayer compliance. (2) E-Samsat Service Based on the processed data, the preparatory behavior control gave a calculated t result of 236 1,984. The E-Samsat service has a positive effect on taxpayer compliance. The taxpayer's compliance is known to have a significant value for the effect of X1.X2 simultaneously on Y is 0.000 0.05 and the calculated F value is1.499 F table (3.09) then the hypothesis is accepted